(untitled) (American Journal of Islam and Society, 2018)
This article is part of Darakhshan Khan’s larger body of work on women in the Tablīghī Jamā‘at, who, as she argues persuasively, have not been given the scholarly attention they deserve (barring a few notable exceptions, among them Metcalf 2000). Khan observes that the reasons for this range from the fact that the public image of the Tablīghī Jamā‘at is that of itinerant males, not females, and that gender segregation in South Asian Muslim communities makes women invisible to male scholars. Moreover, in today’s post-9/11 world the Tablīghī Jamā‘at is often viewed through the lens of counter-terrorist concerns. Khan’s article revolves around several key themes: the geographical mobility of Muslim bureaucrats in late nineteenth-century British India; changes in the structure of the family; changing patterns of religious leadership in British India, resulting in part from the creation of seminaries such as the Dār al-‘Ulūm, Deoband; and the incorporation of Muslim women in religious leadership roles in Tablīghī networks from the mid-twentieth century onward. The article seems to fall into two distinct parts. The first half deals with Muslim men from ashraf families working in British Indian government jobs in the late nineteenth century who moved constantly (with their wives and children) in response to bureaucratic postings, living westernized lives at the margins of highly stratified British Indian social networks. Drawing on sources ranging from Urdu literature to biographies, Khan shows how isolating this was for the wives and sometimes professionally disappointing for the husbands. The second half of the article deals with Muslim religious elites and their more limited geographical travels in British India in pursuit of religious knowledge, often coinciding with ...